A bio-inspired real-time capable artificial lateral line system for freestream flow measurements. (3rd June 2016) - Abels, C; Qualtieri, A; Vittorio, M De; Megill, W M; Rizzi, F
Abstract: To enhance today's artificial flow sensing capabilities in aerial and underwater robotics, future robots could be equipped with a large number of miniaturized sensors distributed over the surface to provide high resolution measurement of the surrounding fluid flow. In this work we show a linear array of closely separated bio-inspired micro-electro-mechanical flow sensors whose sensing mechanism is based on a piezoresistive strain-gauge along a stress-driven cantilever beam, mimicking the biological superficial neuromasts found in the lateral line organ of fishes. Aiming to improve state-of-the-art flow sensing capability in autonomously flying and swimming robots, our artificial lateral line system was designed and developed to feature multi-parameter freestream flow measurements which provide information about (1) local flow velocities as measured by the signal amplitudes from the individual cantilevers as well as (2) propagation velocity, (3) linear forward/backward direction along the cantilever beam orientation and (4) periodicity of pulses or pulse trains determined by cross-correlating sensor signals. A real-time capable cross-correlation procedure was developed which makes it possible to extract freestream flow direction and velocity information from flow fluctuations. The computed flow velocities deviate from a commercial system by 0.09 m s −1 at 0.5 m s −1 and 0.15 m s −1 at 1.0 m s −1 flow velocity for a sampling rate of 240 Hz and a sensor distance of 38 mm. Although experiments were performed in air, the presented flow sensing system can be applied to underwater vehicles as well, once the sensors are embedded in a waterproof micro-electro-mechanical systems package.